Is There Asymmetry in the Relationship Between Government Consumption Dynamics and Economic Activity? Evidence From G7 Economies - Senekovič, Marko (Naše gospodarstvo/Our economy, 2021)
In this paper, based on a quarterly dataset of G7 countries with the application of a nonlinear ARDL model we test for the presence of a short-run and long- term asymmetry in the relationship between government spending and economic activity. The main aim of this study is to analyze the relationship between government spending and economic activity in two separate scenarios, first, in periods when government spending increases and, second, in periods when government spending decreases. Our key findings are, first, the linear model that produces a positive relationship between government consumption and economic activity. Second, in the nonlinear model, more than half of the short- run and long-run coefficients are statistically significant. Third, short-run and long-run asymmetry are detected in four out of seven cases with recognized short-run asymmetry also in the remaining three cases based on graphical analysis. Finally, a negatively inclined short-run asymmetry is detected. The results thus imply a stronger output effect in periods of declining dynamics in government consumption. Future research should be focused on broadening the sample countries and model by adding additional variables.